Towards a mixed approach to justify cartel criminalisation: The particular Chilean experience - Ossa Monge, María Francisca (Revista de Estudios de la Justicia, 2023)
This essay explores the justifications for criminalisation of cartels, both from a retributivist and deterrence-oriented point of view. For those purposes, we theoretically conceptualise the figure of cartels and of criminalisation, analyzing the reasons behind the aims sought by penalising this anticompetitive practice. We further analyze the two classical theories of punishment —just deserts or retributivism, and deterrence or utilitarianism— and the effectiveness of the different possible sanctions before analysing Chile’s particular situation in the context of this discussion. Historically, cartels were penalised from the introduction of this anticompetitive practice, only to be decriminalised in the first decade of the 2000s, period incidentally followed by the highest-profile cartel cases in Chile so far, which led to the reinstatement of the criminal sanction for cartels. We focus on how the legislative discussion for this reinstatement provides an insight of the impact that cartel cases inflicted on the Chilean society, and how, despite the fact that the framework of the legislative discussion was mainly focused on deterrence as the objective sought by the criminalisation, retributivist or just deserts connotations of the discussion are useful to infer a mixed approach in what came to be the actual configuration of the criminal figure of the cartel in Chile, which has not been applied to this day, almost a decade after its reinstatement.